1999
DOI: 10.1053/euhj.1998.1352
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and prognostic significance of atrial fibrillation/-flutter following acute myocardial infarction

Abstract: Atrial fibrillation/-flutter often occurs after acute myocardial infarction and our analysis demonstrated that it was an independent predictor of an increased short and long-term mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
136
1
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(159 citation statements)
references
References 0 publications
15
136
1
7
Order By: Relevance
“…In previous studies, AF was frequently associated with advanced age in patients with MI. 8,17 Atrial fibrillation in the elderly may be related to the increased incidence of agerelated coexisting pathologic changes in the noninfarcted myocardium and atrial tissue. In patients with AMI, the multiple etiological factors of atrial arrhythmias have been documented.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, AF was frequently associated with advanced age in patients with MI. 8,17 Atrial fibrillation in the elderly may be related to the increased incidence of agerelated coexisting pathologic changes in the noninfarcted myocardium and atrial tissue. In patients with AMI, the multiple etiological factors of atrial arrhythmias have been documented.…”
Section: Discussionmentioning
confidence: 99%
“…5) As compared with AMI patients with normal sinus rhythm, AMI patients with new-onset AF have been shown to have worse baseline characteristics, more complicated hospital courses, and unfavorable clinical outcomes such as higher incidences of advanced congestive heart failure (CHF), cardiac embolic stroke, and mortality. 1,[6][7][8][9][10]) Surprisingly, all of these studies were conducted in the prethrombolytic or thrombolytic eras. 1,[6][7][8][9][10] Evidence-based medicine has demonstrated that primary percutaneous coronary intervention (PCI) is superior to thrombolytic therapy in terms of increasing the successful reperfusion rate, reducing the incidences of recurrent ischemia and reinfarction, and improving prognostic outcome in patients with acute ST-segment elevation myocardial infarction (STEMI).…”
Section: T He Incidence Of New-onset Atrial Fibrillation (Af) Is Re-mentioning
confidence: 99%
“…1,[6][7][8][9][10]) Surprisingly, all of these studies were conducted in the prethrombolytic or thrombolytic eras. 1,[6][7][8][9][10] Evidence-based medicine has demonstrated that primary percutaneous coronary intervention (PCI) is superior to thrombolytic therapy in terms of increasing the successful reperfusion rate, reducing the incidences of recurrent ischemia and reinfarction, and improving prognostic outcome in patients with acute ST-segment elevation myocardial infarction (STEMI). [11][12][13][14] Additionally, one previous study has found that AF was not a significantly independent predictor for short-and long-term outcomes after PCI in the setting of chest pain syndrome.…”
Section: T He Incidence Of New-onset Atrial Fibrillation (Af) Is Re-mentioning
confidence: 99%
“…Esse tipo de arritmia tem incidência que varia de 10%-22% entre os pacientes na evolução do infarto agudo do miocárdio, sendo muito mais comum entre os idosos 459 e aqueles com disfunção ventricular 460 .…”
Section: -Fibrilação Ou Flutter Atrialunclassified